Design Numbers-Recognizing Game with Interactive Projection for Young Children - Nurindiyani, Artiarini Kusuma; Muhammad, Farhan; Annisa, Fardani; Basukli, Achmad; Fadhliana, Nisa Rizqiya (Universitas Pendidikan Indonesia (UPI), 2023)
Early Childhood Education (PAUD) requires an interactive and attractive learning system. The PAUD learning method is also capable of stimulating the knowledge development of the students, especially in the cognitive aspect. Such an aspect enters into an educational game where there is an element of education obtained from something that exists and is inherent as well as being part of the game itself. The activities that have these educational elements can stimulate and train the development of the child's brain and stimulate the creativity of children's thinking. The use of technology has a strong influence on the development of education in children of PAUD age. Interactive Projection is one of the learning media for students to understand numbers easily and fun. Target kids are there at the age of three to five, with introductions starting from physical numbers, how to write numbers, counting some objects and matching numbers. Numberpedia uses blackbox method as a testing method. From the blackbox method, some several questions were carried out to support functional testing, a percentage value of 90% was obtained.